2010
DOI: 10.1016/j.plantsci.2010.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Tomato is a suitable material for producing recombinant miraculin protein in genetically stable manner

Abstract: Miraculin is a taste-modifying protein that turns sour tastes into sweet ones. We previously generated transgenic tomato plants that constitutively expressed miraculin. To study the stability of transgene inheritance and expression in detail, three lines of transgenic tomato that highly accumulate miraculin in the T0 generation with a single copy of the miraculin gene were analyzed for genomic organization, mRNA expression and miraculin accumulation up to the T5 generation, corresponding to six generations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 19 publications
0
25
0
3
Order By: Relevance
“…The cost of downstream processing of plant‐derived recombinant proteins is reported to account for about 80% of the total expenditure (Buonaguro and Butler‐Ransohoff, ; Kusnadi et al ., ). However, using watery tissues such as tomatoes as the production platforms has the potential of reducing the cost, as they are easier to extract than dry tissues such as cereals (Schillberg et al ., ; Yano et al ., ). The present study shows that purifying r‐protein from sugarcane juice not only provides appreciable yield but can also ultimately reduce the purification cost.…”
Section: Discussionmentioning
confidence: 97%
“…The cost of downstream processing of plant‐derived recombinant proteins is reported to account for about 80% of the total expenditure (Buonaguro and Butler‐Ransohoff, ; Kusnadi et al ., ). However, using watery tissues such as tomatoes as the production platforms has the potential of reducing the cost, as they are easier to extract than dry tissues such as cereals (Schillberg et al ., ; Yano et al ., ). The present study shows that purifying r‐protein from sugarcane juice not only provides appreciable yield but can also ultimately reduce the purification cost.…”
Section: Discussionmentioning
confidence: 97%
“…Among the miraculinaccumulating transgenic tomato lines, a line that we named 56B had a single copy of the miraculin transgene and accumulated miraculin to high levels in the T 0 generation. Line 56B was propagated up to the T 5 generation, which corresponds to six generations (Yano et al 2010). That study showed that miraculin transgene inheritance and expression were stable through multiple generations in transgenic tomatoes.…”
mentioning
confidence: 99%
“…"Moneymaker"), which contain the miraculin gene (AB512278) driven by the CaMV 35S promoter-nos terminator cassette in the pBI121 vector and accumulate high concentrations of miraculin in the entire plant, have previously been produced and evaluated for their miraculin contents (Sun et al 2007;Yano et al 2010). The seeds of transgenic tomatoes and non-transgenic wild-type (WT) tomatoes were germinated on Petri dishes covered with moist filter paper at 25°C with a 16 h light/8 h dark cycle.…”
Section: Miraculin-accumulating Transgenic Tomatomentioning
confidence: 99%